Computer games and sociocultural play: An activity theoretical perspective - Ang, Chee Siang; Zaphiris, Panayiotis; Wilson, Stephanie (My University, 2010)
Various forms of play emerge around computer games. These types of play, known as out-of-game play or extrinsic play, take place beyond the original game context. Despite their significant contribution to the overall play experience, they are often neglected by the game research community. Conventional game theories such as ludology and narratology do not provide an insightful account of the sociocultural aspects of game play. Therefore, in this article, we report our observations and investigations into different forms of extrinsic play activities in an online virtual setting. Founded on activity theory, we articulate theoretical models that explicate game play in a sociocultural context. Our findings reveal that extrinsic play constitutes reflective play and expansive play, which transform the play activity and transport the players beyond the original boundary of play.
Keywords: Activity theory; Computer games; Extrinsic play; Sociocultural play